The longitudinal study of intellectual capital efficiency and firm performance: the moderating effect of innovation / Azlina Rahim - Rahim, Azlina (2019)
In the knowledge economy, intellectual capital (IC) has become one of the primary sources of competitive advantage for a firm. Intellectual capital which consists of a set of intangibles drives the organizational performance and value creation. Therefore, it is important to understand whether the resource is being efficiently utilized by the companies to their advantage, especially in creating the value over time. The main objective of this thesis is to empirically examine the relationship between intellectual capital efficiency and its components namely human capital efficiency, structural capital efficiency and capital employed efficiency of the Malaysian companies. Intellectual capital efficiency is measured using Pulic's Value Added Intellectual Coefficient (VAIC) through quantitative approach. The empirical data were drawn from a panel consisting of 767 firms-year observation companies listed in the Bursa Malaysia Main Market, from several different industries, observed over the thirteenyear period from 2002 to 2012. In addition, this study also investigates the moderating effect of innovation on the intellectual capital efficiency and firms' performance. This study used statistical methods such as correlation and regression to analyze the data. Direct and moderating relationships between value added intellectual coefficient, human capital efficiency, structural capital efficiency and capital employed efficiency and five measures of performance are statistically analysed. The regression models were constructed to examine the relationship between intellectual capital efficiency and firms' market-to-book value ratios, and explore the relation between intellectual capital and firms' performance. The results obtained through testing the research hypotheses show that there is a positive and meaningful relationship between the variables. It suggests that there is a direct relationship between intellectual capital efficiency and performance of Malaysian publicly listed firms. It is revealed that intellectual capital efficiency of Malaysian companies is contributed by human capital efficiency followed by structural capital efficiency and capital employed efficiency. The results also suggest the possibility of a moderating relationship of innovation which impacts on firm performance. In addition, the results reveal that there is significant difference in the intellectual capital efficiency among different industries in Malaysia. The empirical investigation of these relationships in the context of the Malaysian economy enriches the literature. The results of the study also provide useful insights to regulators, professional bodies, policy makers, practitioners and academics that are relevant to their future decisions. In addition, the findings help companies reallocate intellectual resources properly since it is a way to enhance superior performance and building sustainable advantages in emerging economies.